1977
DOI: 10.2307/525893
|View full text |Cite
|
Sign up to set email alerts
|

Gold-in-Glass Beads from the Ancient World

Abstract: By GEORGE C. BOON S OME years ago, with the encouragement of Dr D. B. Harden, I began the pursuit of a type of segmented bead apparently rare in Romano-British contexts, but curiously frequent in the graves of Meroitic Faras. A preliminary note appeared in 1966; 1 now, there is much to add, including (by the generosity of Dr Maria Dekowna and Mme Hanna Pawtowska of the Institute of the History of Material Culture, Polish Academy of Sciences) analyses which in two cases hint at a common origin. But Faras and Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 2 publications
1
7
0
1
Order By: Relevance
“…Production of metal‐in‐glass beads is usually associated with Hellenistic and Roman Mediterranean workshops (e.g., Spaer ). This has been confirmed by chemical composition studies that revealed the use of natron glass in their production, as also evidenced for the Lower Nubia finds (e.g., Boon and Dekówna , 203, tab. 1).…”
Section: Resultssupporting
confidence: 61%
“…Production of metal‐in‐glass beads is usually associated with Hellenistic and Roman Mediterranean workshops (e.g., Spaer ). This has been confirmed by chemical composition studies that revealed the use of natron glass in their production, as also evidenced for the Lower Nubia finds (e.g., Boon and Dekówna , 203, tab. 1).…”
Section: Resultssupporting
confidence: 61%
“…Based on site context, radiocarbon dates and research, 5 the beads were initially suggested to be Greco-Roman (100 BC-400 AD). However, Chami's subsequent research revealed that gold-glass beads were made for over 1500 years and were produced well into the medieval period (Boon 1977;Spaer 1993). Finally, based on the position of the Mkukutu beads in the site, Chami concluded that they were 3rd century Roman.…”
Section: Recent Studiesmentioning
confidence: 99%
“…Finger-rings are frequent grave finds in Britain and may represent items simply left on the body at burial. 61 In contrast, earrings are rare finds in graves, although they may be misidentified in 48 Cool 2004, 389. 49 Boon 1977;Guido 1979;Cool 2004;2010;Eckardt 2014, 45-50, fig. 2 Cool 1983, 23-8.…”
Section: Discussionmentioning
confidence: 99%